Effectiveness of stereotactic body radiotherapy for portal vein tumor thrombosis in patients with hepatocellular carcinoma and underlying chronic liver disease. Issue 3 (5th August 2020) - Choi, Hoon Sik; Kang, Ki Mun; Jeong, Bae Kwon; Jeong, Hojin; Lee, Yun Hee; Ha, In Bong; Song, Jin Ho
Abstract: Aim: Stereotactic‐body radiotherapy (SBRT) is a treatment option for portal vein tumor thrombosis (PVTT) in patients with hepatocellular carcinoma (HCC). Here, we report on our experience of treating PVTT using SBRT in patients with concomitant underlying chronic liver disease. Methods: This study included 24 patients. The initial prescription dose was 45 Gy in three fractions in 17 (70.8%) patients, but it was modified in the remaining seven (29.2%) patients, with the dose ranging from 39 to 42 Gy in 3‐4 fractions. After SBRT, transarterial chemoembolization (TACE) was performed in 16 (66.7%) patients. Results: Of the 24 patients, 2 (8.3%) showed complete response, while 11 (45.8%) showed partial response. After a median follow‐up of 8.4 months (range: 2.6‐56.5 months), the 1‐year overall survival (OS) and the median survival were 67.5% and 20.8 months, respectively. Both combined SBRT and TACE and grade ≥3 hepatic toxicity affected the 1‐year OS (SBRT alone vs SBRT + TACE: 14.6% vs 71.4%, P < .001; presence of hepatic toxicity vs absence: 0% vs 81.1%, P = .002). Conclusions: Overall, SBRT, especially in combination with TACE, is an effective treatment for patients with HCC and PVTT. An optimal dose schedule must be followed to reduce hepatic toxicity while maintaining tumor response.